Hepatoprotective Effects of Royal Jelly Against Vincristine-Induced Hepatotoxicity in Rats: A Biochemical and Molecular Study - Rahime Erzincan; Cuneyt Caglayan; Fatih Mehmet Kandemir; Ebubekir İzol; Cihan Gür; Mustafa İleritürk (Life)
Vincristine (VCR) is a chemotherapeutic agent classified as a vinca alkaloid. Royal jelly (RJ) is a significant bee product produced by worker bees, characterized by its high protein content. This study aims to investigate the protective effects of RJ against VCR-induced liver damage. VCR was intraperitoneally administered at a dose of 0.1 mg/kg body weight (b.w.) and RJ was orally administered at doses of 150 and 300 mg/kg b.w. Both treatments were applied to the rats on days 1–6 and 9–14. The composition of RJ was analyzed using LC-MS/MS, revealing the presence of 15 different phytochemical compounds with strong antioxidant properties. Serum samples obtained from the rats were analyzed for ALT, ALP, and AST levels. While these enzyme levels were significantly elevated in the VCR group, a notable reduction was observed following RJ administration. Additionally, SOD, CAT, GPx, and GSH antioxidant parameters, along with MDA levels, were evaluated in liver tissue samples. The results indicated a decrease in SOD, CAT, GPx, and GSH activities/levels and an increase in MDA levels in the VCR group. Furthermore, ELISA was used to assess JAK2, STAT3, and mTOR/PI3K/AKT signaling pathways. VCR administration led to a decrease in mTOR/PI3K/AKT levels and an increase in JAK2 and STAT3 levels. In addition, the mRNA transcription levels of inflammation (NF-κB, TNF-α, and IL-1β), endoplasmic reticulum (ER) stress (IRE-1, GRP78, PERK, and ATF-6), and autophagy markers (LC3A and LC3B) were examined. A significant increase in inflammation, ER stress, and autophagy-related markers was observed in the VCR-treated group. Lastly, the protein expression levels of Bax, Bcl-2, Caspase-3, and NF-κB were evaluated. VCR treatment increased Bax, Caspase 3, and NF-κB levels, whereas Bcl-2 levels were decreased. However, following RJ administration, all these parameters were reversed, demonstrating significant improvements. In conclusion, these findings suggest that RJ may exert a protective effect against VCR-induced liver damage.